Decoding Marketing Mix Effects: Insights from Indonesia - Sari, Herlinda Maya Kumala; Randusiwi, Rejekining (Indonesian Journal Publisher, 2024)
This study investigates the efficacy of the marketing mix strategy in boosting sales to customers in the Sidoarjo area, addressing a gap in understanding its impact on local consumer behavior. Utilizing a descriptive quantitative approach, data was gathered from 96 respondents through a structured questionnaire offering five response options, analyzed using SmartPLS 3.0 software. The results indicate that product quality significantly enhances consumer acceptance, positively influencing sales. Additionally, the study confirms that other marketing mix elements such as place (access), price, and promotion also significantly contribute to the success of marketing strategies by ensuring good accessibility, affordability, and effective promotional activities. These findings suggest that a well-coordinated marketing mix can effectively drive sales performance in regional markets.